Full endoscopic surgery for thoracic pathology: an assessment of supportive evidence. Issue 1 (January 2021) - Gibson, Rory D. S.; Wagner, Ralf; Gibson, J. N. Alastair
Abstract : In the last five years, surgeons have applied endoscopic transforaminal surgical techniques mastered in the lumbar spine to the treatment of thoracic pathology. The aim of this systematic review was to collate the available literature to determine the place and efficacy of full endoscopic approaches used in the treatment of thoracic disc prolapse and stenosis. An electronic literature search of PubMed, Embase, the Cochrane database and Google Scholar was performed as suggested by the Preferred Reporting Items for Systematic Review and Meta-analysis statements. Included were any full-text articles referring to full endoscopic thoracic surgical procedures in any language. We identified 17 patient series, one cohort study and 13 case reports with single or of up to three patients. Although the majority included disc pathology, 11 papers related cord compression in a proportion of cases to ossification of the ligamentum flavum or posterior longitudinal ligament. Two studies described the treatment of discitis and one reported the use of endoscopy for tumour resection. Where reported, excellent or good outcomes were achieved for full endoscopic procedures in a mean of 81% of patients (range 46–100%) with a complication rate of 8% (range 0–15%), comparing favourably with rates reported after open discectomy (anterior, posterolateral and thoracoscopic) or by endoscopic tubular assisted approaches. Twenty-one of the 31 author groups reported use of local anaesthesia plus sedation rather than general anaesthesia, providing 'self-neuromonitoring' by allowing patients to respond to cord and/or nerve stimuli. Cite this article: EFORT Open Rev 2021;6:930-940. DOI: 10.1302/2058-5241.6.200080